Application of Apriori to Determine Correlations between Source Competencies Human Resources with Education and Working Period - Reza Alexandra; Buaton, Relita; Suria Alamsyah Putra (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Human resource competence (HR) is a key factor in supporting organizational performance. Referring to several problems in the Binjai City BKD, such as there is a difference between the competencies possessed by employees and the competencies needed to carry out their duties and responsibilities effectively, the placement of employees that are not in accordance with the competencies, the absence of a system to map and monitor employee competencies can cause difficulties in identifying development needs, as well as in the placement of appropriate employees. Employee competency mapping is relevant in the implementation of human resource management, both in planning, development and employee placement activities. Therefore, it is necessary to carry out competency mapping that can be used for various human resource management needs and this is in accordance with the priority program that will be carried out in the 2025 RKPD, namely improving the quality of innovative human resources. This study uses a priori algorithm with the Rapidminer application to be able to provide correlation results of human resource competencies. From the results of the research, a correlation was formed between human resource competence and education and work period, namely 8 association rules and the highest best rule was obtained with support of 32% and confidence value of 99.4%.